The organisation of primary health care service delivery for non-communicable diseases in Nigeria: A case-study analysis - Whenayon Simeon Ajisegiri; Seye Abimbola; Azeb Gebresilassie Tesema; Olumuyiwa O. Odusanya; David Peiris; Rohina Joshi (Public Library of Science (PLoS), 2022)
As chronic diseases, non-communicable diseases (NCDs) require sustained person-centred and community-based care. Given its direct link to communities and households, Primary Health Care (PHC) is well positioned to achieve such care. In Nigeria, the national government has prioritized PHC system strengthening as a means of achieving national NCD targets. However, strengthening PHC systems for NCDs require re-organization of PHC service delivery, based on contextual understanding of existing facilitators and barriers to PHC service delivery for NCDs. We conducted a mixed method case study to explore NCD service delivery with 13 PHC facilities serving as the cases of interest. The study was conducted in two northern and two southern states in Nigeria-and included qualitative interviews with 25 participants, 13 focus group discussion among 107 participants and direct observation at the 13 PHCs. We found that interprofessional role conflict among healthcare workers, perverse incentives to sustain the functioning of PHC facilities in the face of government under-investment, and the perception of PHC as an inferior health system were major barriers to improved organisation of NCD management. Conversely, the presence of physicians at PHC facilities and involvement of civil society organizations in aiding community linkage were key enablers. These marked differences in performance and capacity between PHC facilities in northern compared to southern states, with those in the south better organised to deliver NCD services. PHC reforms that are tailored to the socio-political and economic variations across Nigeria are needed to improve capacity to address NCDs.